2021
DOI: 10.1016/j.isci.2021.102481
|View full text |Cite
|
Sign up to set email alerts
|

Reinvigorating electrochemistry education

Abstract: Electrochemistry is an established discipline with modern frontiers spanning energy conversion and storage, neuroscience, and organic synthesis. In spite of the expanding opportunities for academic and industrial electrochemists, particularly in the growing energy-storage sector, rigorous training of electrochemists is generally lacking at academic institutions in the United States. In this perspective, we highlight the core concepts of electrochemistry and discuss ways in which it has been historically taught… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 41 publications
0
44
0
1
Order By: Relevance
“…In this new laboratory course, students may for instance learn how new generation nanostructured electrodes are ideally suited for employment in new continuous-flow electroreactors making electrosynthesis highly efficient and truly "green". 36,37 New tools to enhance education span from today's inexpensive electronics and open-source software, 3 through magnetic resonance imaging for probing electrochemical processes in a model electrochemical cell. 38 From a conceptual viewpoint, however, better undergraduate education in electrochemistry requires educators to improve their ability "to support and guide students in developing a metavisual competence for visualizing" 15 electrochemical phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this new laboratory course, students may for instance learn how new generation nanostructured electrodes are ideally suited for employment in new continuous-flow electroreactors making electrosynthesis highly efficient and truly "green". 36,37 New tools to enhance education span from today's inexpensive electronics and open-source software, 3 through magnetic resonance imaging for probing electrochemical processes in a model electrochemical cell. 38 From a conceptual viewpoint, however, better undergraduate education in electrochemistry requires educators to improve their ability "to support and guide students in developing a metavisual competence for visualizing" 15 electrochemical phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Kempler and co-workers recently reported that "rigorous training of electrochemists is generally lacking at academic institutions in the United States". 3 The team thereby suggested avenues to reinvigorate electrochemistry education based on today's inexpensive electronics and open-source software providing new tools for teaching electrochemistry interdisciplinary concepts. 3 Similar findings were reported in 2019 by Tsaparlis in Greece noting that electrochemistry was a "hard subject for students" 4 due to complexity and plurality of its concepts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 Additionally, given the disruptions to learning encountered during the COVID-19 pandemic, many students have indicated that they have had little opportunity to study and explore electrochemical methods pre-university; developing opportunities to explore these in a practical setting would be of significant benefit to their understanding of this conceptually troublesome topic. 17 By carrying out an electrochemical synthesis practically, the ideas introduced at school can be expanded upon. This allows discussion and clarification of key concepts such as anode and cathode redox behavior and the importance of the electrolyte, further cementing students' understanding of this area of chemistry.…”
Section: ■ Introductionmentioning
confidence: 99%